Peculiarities of heart rate variability in 14-16 year-old football players - Pseunok, A. A.; Mugotlev, M. A.; Silantiev, M. N.; Gasanova, R. A. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze the peculiarities of heart rate variability-based adaptation of young athletes to training loads. Methods and structure of the study. The study involved the 14-16 year-old football players and was carried out in those periods of the academic year that were the farthest from the holidays. By the end of the experiment, the sports experience of the respondents was 6 years. The RG athletes were trained in the traditional motor mode (two physical education lessons a week). Results and discussion. The results obtained show that under the influence of the extended motor mode the resting heart rate structure changes, thus reflecting the processes of formation of new, more favorable relations: a decrease in the sympathetic and an increase in the parasympathetic influences on the heart. We also detected a stable reaction of the body of young football players to increased motor activity, which was interpreted as an adaptive response. With increasing physical fitness level, it is the autonomous regulation circuit that starts to prevail; the heart rate regulation mechanisms become decentralized and the tone of the sympathetic nervous system decreases, while the central mechanisms of heart rate regulation increases due to overtraining. Conclusion. The data obtained can be effectively used in sports selection, training process management, prediction of overtraining and overstrain.